Web Technologies and Applications APWeb 2012 International Workshops: SenDe, IDP, IEKB, MBC, Kunming, China, April 11-13, 2012. Proceedings - Wang, Hua.; Zou, Lei.; Huang, Guangyan; He, Jing.; Pang, Chaoyi; Zhang, Hao Lan.; Zhao, Dongyan; Yi, Zhuang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of 4 international workshops held in conjunction with the 14th Asia-Pacific Web Conference, APWeb 2012, in Kunming, China, in April 2012 (see LNCS 7235). The 29 revised full papers presented were carefully reviewed and selected for presentation at the following 4 workshops: the 1st workshop on sensor networks and data engineering (SenDe 2012), the 1st international workshop on intelligent data processing (IDP 2012), the 1st international workshop on information extraction and knowledge base building (IEKB 2012), and the 3rd international workshop on mobile business collaboration (MBC 2012).
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Computer Communication Networks; Database Management; Data Mining and Knowledge Discovery